Sarcopenia and hospitalisation costs in older adults: a cross-sectional study - Ana C. Antunes (2017)
Aim: The impact of sarcopenia on hospitalisation has been under intense investigation; however, little is known about the association between sarcopenia and their costs among hospitalised patients. The aim of the present study was to quantify the association between sarcopenia and hospitalisation costs among older adults.Methods: A cross-sectional study was conducted in 201 hospitalised older adults in a general hospital. Sarcopenia was identified according to the European Working Group on Sarcopenia in Older People (EWGSOP) criteria. Muscle mass was assessed by anthropometric measurements, muscle strength through handgrip strength evaluation and physical performance by Timed Up and Go Test. Nutritional status was evaluated using the Mini Nutritional AssessmentShort Form (MNA-SF), and hospital costs were assessed with the Diagnosis Related Groups (DRGs) system. Multivariable logistic regression models were fitted to quantify the association between sarcopenia and hospital costs. Increased hospital costs were considered when a patients0 cost was higher than the mean cost of an average patient (2396.24).Results: Within this sample, 10.4% sarcopenic, 43.8% at nutritional risk and 14.9% undernourished older adults were identified. After adjustment, sarcopenia (OR = 5.70, 95% CI 1.57-20.71) and low muscle strength (OR = 2.40, 95% CI 1.12-5.15) were associated with increased hospital costs.Conclusions: Sarcopenia and low muscle strength at hospital admission were independently associated withincreased hospital costs.